Nexus antara Fundamentalisme Islam dan Terorisme - Chaider S. Bamualim; Ridwan al-Makassary (Program Studi Ilmu Agama Islam Program Magister, Universitas Islam Indonesia, 2006)
Terrorism is an old phenomenon that has been strengthened today. Several acts of terror that have occured all over the world, especially in Indonesia, have created a sense of fear. Now, acts of terror which can be justified by religion have gained momentum. Such acts are almost always identified as being in some way related to Islam. The big question here is why the religion of Islam has been used in this way, that is as justification for terrorism. This paper elaborates on this issue, investigating some specific cases. First, it examines the difficulties of dining terror ism, and then discusses the nexus between religion and terrorism. Lastly, it concludes that Islam is indeed not a religion that condones terrorism.